Lymphocyte‐to‐C‐reactive protein ratio and score in patients with heart failure: Nutritional status, physical function, and prognosis - Daichi Maeda; Yuya Matsue; Nobuyuki Kagiyama; Yudai Fujimoto; Tsutomu Sunayama; Taishi Dotare; Taisuke Nakade; Kentaro Jujo; Kazuya Saito; Kentaro Kamiya; Hiroshi Saito; Yuki Ogasahara; et al. (ESC Heart Failure)
Abstract Aims In heart failure (HF), inflammation is linked to malnutrition and impaired physical function. In this study, we aimed to assess how novel nutritional–inflammatory markers and lymphocyte‐to‐C‐reactive protein ratio (LCR) and score (LCS) are associated with the nutritional status, physical function, and prognosis of patients with HF. Methods and results This study was a secondary analysis of the FRAGILE‐HF study, a prospective observational study conducted across 15 hospitals in Japan. We included 1212 patients (mean age, 80.2 ± 7.8 years; 513 women) hospitalized with HF, who were classified into three groups according to their LCS score: 0 (n = 498), 1 (n = 533), and 2 (n = 181). Baseline data on physical examination, echocardiography, blood test results (including lymphocyte counts and CRP levels), and oral medication usage were collected in a clinically compensated state before discharge. Nutritional status and physical function were evaluated using several indices and tests. The primary outcome of this study was all‐cause death within 2 years. Univariate and multivariate linear regression analyses were performed to evaluate the associations among the nutritional status, physical function, and LCR/LCS. Patients with an LCS score of 2 were older and had a lower body mass index than those in the other two groups. Multivariate linear regression analysis revealed that lower LCR and higher LCS were independently associated with worse nutritional status, lower handgrip strength, shorter physical performance battery score, and shorter 6‐min walk distance. At 2 years, all‐cause death occurred in 254 patients: 86 (17.6%), 113 (21.5%), and 55 (30.9%) with LCS scores of 0, 1, and 2, respectively (P = 0.001). Cox proportional hazards analysis revealed that LCR and LCS were significantly associated with 2‐year mortality even after adjusting for the conventional risk model (LCS score, 0 vs. 2: hazard ratio, 1.64; 95% confidence interval [CI]; 1.14–2.35; P = 0.007; log‐transformed LCR: hazard ratio, 0.88; 95% CI, 0.81–0.95; P = 0.002). LCR yielded additional prognostic predictability compared with the conventional risk model (continuous net reclassification improvement, 0.153; 95% CI, 0.007–0.299; P = 0.041). Conclusions LCR and LCS emerge as potential predictors of nutritional status, physical function, and prognosis in older patients with HF.